(untitled) (Research, Society and Development, 2021)
The objective of this research was to evaluate the best type and adequate content of adhesive in low density particleboards produced with corn cob, in addition to the chemical analysis of the particles. The adhesives used were urea-formaldehyde (UF) and phenol-formaldehyde (PF) distributed in three levels (6, 9 and 12%) on the dry mass of the particles and the nominal density was 0.60 g.cm-3. Regarding the water absorption and swelling properties, no significant differences were found between treatments. The mean value calculated for the IE 24 h was 37.07%, being above the minimum limit stipulated by the standard. The modulus of rupture (MOR) and modulus of elasticity (MOE), were influenced by the tested factors. All particleboards met the requirements of the standard norm. For internal adhesion there was a significant effect only for the type of adhesive factor, with the particleboards produced with PF showing the highest means. For the compression property there was no effect of the factors tested. In general, the dimensional stability of the particleboards was below the minimum required by the standard, but the mechanical properties met all requirements.